A scoping review of preclinical intensive care unit-acquired weakness models - Yu, Qingmei; Song, Jiamei; Yang, Luying; Miao, Yanmei; Xie, Leiyu; Ma, Xinglong; Xie, Peng; Chen, Shaolin (Frontiers in Physiology, 2024)
Background: Animal models focusing on neuromuscular outcomes are crucial for understanding the mechanisms of intensive care unit-acquired weakness (ICU-AW) and exploring potential innovative prevention and treatment strategies.To analyse and evaluate preclinical ICU-AW models.: We manually searched five English and four Chinese databases from January 1, 2002, to February 1, 2024, and reviewed related study references. Full-text publications describing animal models of muscle weakness and atrophy in critical illness were included. Detailed information about model types, animal species, sex, age, induction methods, outcome measures, drawbacks and strengths was extracted from each included study. Results: A total of 3451 citations were initially retrieved, with 84 studies included in the final analysis. The most frequently studied animal model included rodents (86.9%), 64.3% of which were male animals. ICU-AW animal models were mostly induced by comprehensive intensive care unit (ICU) interventions (38.1%) and sepsis (51.2%). Most studies focused on limb muscles (66.7%), diaphragm muscles (21.4%) or both (9.5%). Reported outcomes primarily included muscular pathological changes (83.3%), electrophysiological examinations of muscles (57.1%) and animal grip strength (16.6%). However, details such as animal age, mortality data, experimental design, randomisation, blinding, sample size and interventions for the experimental group and/or control group were inadequately reported. Conclusion: Many preclinical models are used to study ICU-AW, but the reporting of methodological details is often incomplete. Although current ICU animal models can mimic the characteristics of human ICU-AW, there is no standard model. Future preclinical studies should develop a standard ICU-AW animal model to enhance reproducibility and improve scientific rigor in exploring the mechanisms and potential treatment of ICU-AW.